Psychological Disorders in Children and Adolescents During War: The Role of Psychological First Aid and Recommendations of the Ministry of Health of Ukraine - Barna Ольга; Barna Любов (Psychosomatic Medicine and General Practice, 2025)
This article examines current challenges to the mental health of children and adolescents in the context of the war in Ukraine. Particular attention is given to the provision of psychological first aid based on the “5R” algorithm developed by the Ministry of Health of Ukraine. The paper outlines trauma-related factors, clinical manifestations (PTSD, anxiety, depression), and specific approaches to addressing panic states and suicidal ideation among adolescents. It also highlights effective self-regulation techniques and exercises. Practical recommendations are offered for assisting children in combat conditions.